ANALISIS HUBUNGAN TINGKAT KEMANDIRIAN LANSIA DALAM MELAKUKAN ACTIVITY-DAILY-LIVING (ADL) DENGAN FAKTOR-FAKTOR TERKAIT DI PROVINSI-SUMATERA-BARAT - Erdanela Setiawati; Rosmaini, Rosmaini; Fidiariani Sjaaf; Echa Ismalianti (Nusantara Hasana Journal, 2024)
Background. Many factors are related to the independence of the elderly in fulfilling Activities-of-Daily-Living (ADL), namely age, health status, nutritional status, physical and mental health, history of chronic diseases, immobility, easy to fall, depression, mental and cognitive function, the role of midwives, the role of cadres, the role and support of the family, social, economic, religious conditions, physical activity and the activity of the elderly. Research Objectives. Analyze the relationship between the level of independence of the elderly in carrying out Activities-Daily-Living and related factors. Research Methods. Analytical-quantitative with a cross-sectional design, in August-2023 to January-2024, in Kecamatan-Tigo-Nagari, Kabupaten-Pasaman, Prvinsi-Sumatera-Barat. Purposive-sampling technique, obtained a sample of 105 elderly. KATZ Index research instrument. Univariate and bivariate data analysis using the Chi-square-Test. Results. Univariate analysis, the majority of elderly have the following levels of independence: independent 79 people (75.2%), aged between 60-69 years (Young Elderly) 58 elderly (55.2%) and female 61 elderly (58.1%), low education (elementary school) 90 elderly (85.7%) and previously unemployed 88 elderly (83.8%). The majority of elderly have income 85 elderly (81%), have a spouse 78 elderly (74.3%) and have few chronic diseases (<2) 60 elderly (57.1%). Bivariate analysis, the relationship between 7 related factors (age, gender, education, previous job, income, spouse, and chronic disease) with the level of independence of the elderly, which is significantly related only to income with p-value = 0.001. The strength of the relationship between income and level of independence was assessed from the Odds Ratio (OR)=5.704. While age (p-value=0.193), gender (p-value=0.782), education (p-value=0.348), previous job (p-value=1.000), partner (p-value=0.145), chronic disease (p-value=0.870) were not related. Conclusion. The majority of elderly living in West Sumatra Province have a high level of independence, aged 60-69 years (young elderly), female, low education (elementary school), previously unemployed, have a partner, have income, have few chronic diseases (<2). There is a significant relationship between income and the level of independence of the elderly with p-value = 0.001. Elderly who earn compared to those who do not earn have a 5 times greater chance of increasing the independence of the elderly with OR = 5.704.